2021
DOI: 10.26599/jnr.2021.9040002
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 Yearbook of Neurorestoratology

Abstract: COVID-19 has been an emerging and rapidly evolving risk to people of the world in 2020. Facing this dangerous situation, many colleagues in Neurorestoratology did their best to avoid infection if themselves and their patients, and continued their work in the research areas described in the 2020 Yearbook of Neurorestoratology. Neurorestorative achievements and progress during 2020 includes recent findings on the pathogenesis of neurological diseases, neurorestorative mechanisms and clinical therapeutic achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Despite the availability of over 20 antiepileptic drugs (AEDs) for the symptomatic treatment of epilepsy, approximately one-third of patients with epilepsy have epilepsy refractory to AEDs [2]. It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of over 20 antiepileptic drugs (AEDs) for the symptomatic treatment of epilepsy, approximately one-third of patients with epilepsy have epilepsy refractory to AEDs [2]. It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery for pelvic fractures is complicated, and open reduction and internal fixation of the pelvis is the current standard for the treatment of acetabular fractures [ 3 ]. In addition to the surgical challenge of treating acetabular fractures in the elderly or even trying to restore degenerative changes [ 4 ], the condition of such patients is often accompanied by cardiovascular and cerebrovascular diseases, abnormal glucose metabolism, and compensatory liver and kidney function, which will lead to reduced tolerance for surgery [ 5 ]. Therefore, there is the potential for many postoperative complications and other factors of uncertainty, often leading to the unsatisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…According to vari-ous hospital-based studies [4][5][6], the prevalence of PSCID varies from 11.6% to 56.3%. Therefore, neurorestoration of cognitive impairment has gained increasing interest among researchers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-9 (MMP-9) is a member of the MMP family with 26 extracellular and intracellular matrix-degrading enzymes that regulate many zinc-binding proteolytic enzymes physiological processes, including activation of growth factors, tumor growth and metastasis, cleavage of zymogens, and remodeling of the extracellular matrix [7,8]. MMP-9 is mainly produced by neurons, and its expression and activity have been detected in adult brain structure, such as the hippocampus, cortex, striatum, and cerebellum [9,10]. In neurons, the MMP-9 expression is induced by neuronal activity under both physiological and pathological conditions, such as stroke [11,12] and epilepsy [13].…”
Section: Introductionmentioning
confidence: 99%